Selected Problems of Disaster Theory - Jaroslav SLEPECKÝ; Jiří DUŠEK (Communications of International Proceedings, 2022)
In the article, the authors analyse the problems of the disaster theory as a very important scientific discipline, which was greatly underestimated in the past. The mathematically demanding singularity theory of smooth mapping and the theory of bifurcations of dynamical systems make it difficult to use in practice. The authors present a mathematical model of the disaster theory and suggest its potential application mainly in disaster economy.
Keywords: Bifurcation; economy; disaster economy; disaster; mathematical model of a disaster; disaster theory; singularity theory.